Incidence of suicide by hanging in Klang Valley from 2007 to 2016 - Siti Rahmah Abd Karim; Sri Pawita Albakri Amir Hamzah; Noor Hazfalinda Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia was ranked at 148 by World Health Organization (WHO) in suicide statistic for 2012, where males had a higher tendency to commit suicide, recording a 4.7 per 100,000 in comparison to female (1.5 per 100,000). As hanging is one of the most common methods to commit suicide, this retrospective study was conducted to observe the incidence of suicide by hanging in Klang Valley from four different hospitals. The current study is conducted to provide local database of suicide occurrence by hanging in Klang Valley. A total of 893 suicide cases by hanging from 2007 to 2016 were recorded from post mortem records and analysed. Suicide rates in Klang Valley showed a rising trend from 2007 to 2016. Males from age group 30 to 34 years old and females from 20 to 24 years old have the highest number of suicide fatalities compared to other age groups. Meanwhile, fatalities from the age group of 10 to 14 years old and 80 years old and above showed similar result which is only 7%. 78% of the fatalities were recognized as Malaysian and half of them were Indian. Majority of the victims/cases (45%) who committed suicide by hanging are of Hindu religious denomination. Non-citizen in Malaysia that have the highest suicide rates were from Nepal, Indonesia and Myanmar. Victims also committed suicide more during the day and the peak hours being at 12.00 pm to 5.59 pm.